已知数列{ an }的前n项和Sn满足,Sn=2an+(—1)n,n≥1。
1 。 写出数列{ an }的前三项。
2 。 求数列{ an }的通项公式。
已知数列{ an }的前n项和Sn满足,Sn=2an+(—1)n,n≥1。
1 。 写出数列{ an }的前三项。
2 。 求数列{ an }的通项公式。
由a1+a2=S2=2a2+(-1)²,得a2=0
由a1+a2+a3=S3=2a3+(-1)³,得a2=2
(2)当n≥2时
因为an=Sn-S<n-1>=2(an-a<n-1>)+2×(-1)^n
即an=2a<n-1>-2×(-1)^n=2a<n-1>+2×(-1)^(n-1)
用数列的待定系数法做
设an+λ*(-1)^n=2[a<n-1>+λ*(-1)^(n-1)]
==>an=2a<n-1>+2λ*(-1)^(n-1)-λ*(-1)^n
==>an=2a<n-1>+2λ*(-1)^(n-1)+λ*(-1)^<n-1>
==>an=2a<n-1>+3λ*(-1)^(n-1)
与an=2a<n-1>+2×(-1)^(n-1)对比可得
3λ=2 ==>λ=2/3
所以数列{an+2/3*(-1)^n}是一个公比为2且首项为a1+2/3×(-1)^1=1/3的等比数列
所以an+2/3*(-1)^n=1/3×2^(n-1)
an=1/3×2^(n-1)-2/3*(-1)^n
=2/3×[2^(n-2)-(-1)^n]
=2/3×[2^(n-2)+(-1)^(n-1)]
A1=1
A2=3
A3=7
An=2^n-1